The Jewish religion : a companion - Jacobs, Louis (Oxford ; New York : Oxford University Press, 1995)
Contains a wealth of information on just about every aspect of Jewish belief and practice, both ancient and modern - from personalities in the Bible to Jewish thinkers and writers of the present day, customs, traditions, and Jewish ideas on subjects as diverse as dance, vegetarianism, and eternity
Includes bibliographical references (pages 636-641)
Keywords: Judaism -- Dictionaries; Judaism -- Essence, genius, nature; Judaism